COVID-19-associated mucormycosis and treatments - Vetriselvan Subramaniyan; Shivkanya Fuloria; Hari Kumar Darnal; Dhanalekshmi Unnikrishnan Meenakshi; Mahendran Sekar; Rusli Bin Nordin; Srikumar Chakravarthi; Kathiresan V Sathasivam; Shah Alam Khan; Yuan Seng Wu; Usha Kumari; Kalvatala Sudhakar; et al. (Asian Pacific Journal of Tropical Medicine, 2021)
In the current pandemic, COVID-19 patients with predisposing factors are at an increased risk of mucormycosis, an uncommon angioinvasive infection that is caused by fungi with Mucor genus which is mainly found in plants and soil. Mucormycosis development in COVID-19 patient is related to various factors, such as diabetes, immunocompromise and neutropenia. Excessive use of glucocorticoids for the treatment of critically ill COVID-19 patients also leads to opportunistic infections, such as pulmonary aspergillosis. COVID-19 patients with mucormycosis have a very high mortality rate. This review describes the pathogenesis and various treatment approaches for mucormycosis in COVID-19 patients, including medicinal plants, conventional therapies, adjunct and combination therapies.